Body composition and cardiometabolic disease risk factors in captive baboons (Papio hamadryas sp.): Sexual dimorphism. Issue 1 (6th November 2013) - Higgins, Paul B.; Rodriguez, Perla J.; Voruganti, V. Saroja; Mattern, Vicki; Bastarrachea, Raul A.; Rice, Karen; Raabe, Timothy; Comuzzie, Anthony G.
ABSTRACT Baboons (Papio hamadryas sp.) exhibit significant sexual dimorphism in body size. Sexual dimorphism is also exhibited in a number of circulating factors associated with risk of cardiometabolic disease. We investigated whether sexual dimorphism in body size and composition underlie these differences. We examined data from 28 male and 24 female outdoor group‐housed young adult baboons enrolled in a longitudinal observational study of cardiometabolic disease risk factors. Animals were sedated with ketamine HCl (10 mg/kg) before undergoing venous blood draws, basic body measurements, and dual‐energy X‐ray absorptiometry body composition scans. Percentage glycated hemoglobin A1c (%HbA1c) was measured in whole blood. Serum samples were analyzed for glucose, insulin, C‐peptide, high‐density lipoprotein, and triglyceride concentrations. Males were heavier and had greater body length and lean tissue mass than females. Females had a greater body fat percentage relative to males (10.8 ± 6.4 vs. 6.9 ± 4.0, P = 0.01). Although C‐peptide, fasting glucose, and %HbA1c did not differ between the sexes, females had greater fasting insulin and triglyceride compared to their male counterparts. Insulin and percentage body fat were significantly correlated in males (r = 0.61, P = 0.001) and to a lesser extent in females (r = 0.43, P = 0.04). Overall, relations between adiposity and fasting insulin and fasting triglyceride were stronger in males. After accounting for differences in percentage body fat, fasting insulin and triglyceride were no longer statistically different between males and females. Despite stronger correlations between relative adiposity and insulin and triglyceride in males, the higher fasting insulin and triglyceride of female baboons may be underlain by their greater relative body fat masses. Am J Phys Anthropol 153:9–14, 2014. © 2013 Wiley Periodicals, Inc.